Gestión y Turismo Comunitario en la comunidad Yocón canton Alausí - Arellano Yautivi, Freddy David (2023)
ABSTRACT: The objetive of the research is to analyze the relationship between management and community tourism in the community of Yocón, Alausí canton. The methodology adopts a quantitative and qualitative approach. The type of research is documentary, descriptive, correlational, and field. Finally, the research design is non-experimental and transversal. The instrument applied was a survey based on the independent variable “Management”, evaluating dimensions of planning, organization, direction and control. For the dependent variable “Community Tourism”, it focuses on aspects such as community relations, the appreciation of heritage and equitable distribution. Among the most notable results, 37.50% of the population rate it as regulating the assignment of personnel to contribute to efficiency and performance. On the other hand, 50% described the organizational climate as a regulator for the fulfillment of activities in the community, finally 55.56% considered education and awareness as a regulator for the development of community tourism in a sustainable environment in the community, which allowed us to deduce how the management of community tourism impacts the community of Yocón. It is concluded that there is no relationship between management and community tourism, since the level of management does not guarantee adequate training of personnel to provide experiences to tourists who visit the community.